Quantifying Plant-Borne Carbon Assimilation by Root-Associating Bacteria - Spenser Waller; Stacy L. Wilder; Michael J. Schueller; Alexandra B. Housh; Richard A. Ferrieri (Microorganisms, 2020)
Herbaspirillum seropedicae is a rhizobacteria that occupies a specialized ecological niche in agriculture. As an endophyte and prolific grass root colonizer it has the potential to promote plant growth, enhancing crop yield in many cereal crops. While the mechanisms for plant growth promotion are controversial, the one irrefutable fact is these microorganisms rely heavily on plant-borne carbon as their main energy source in support of their biological functions. Unfortunately, the tools and technology enabling researchers to trace carbon exchange between plants and the microorganisms associating with them has been limiting. Here, we demonstrate that radioactive 11CO2 administered to intact maize leaves with translocation of 11C-photosynthates to roots can provide a ‘traceable’ source of carbon whose assimilation by microbial organisms can be quantified with enormous sensitivity. Fluorescence root imaging of RAM10, a green fluorescent protein (GFP) reporting strain of H. seropedicae, was used to identify regions of high microbial colonization. Microbes were mechanically removed from these regions via sonication in saline solution and extracts were subjected to fluorescence measurement and gamma counting to correlate carbon-11 atoms with numbers of colony forming units. The method has potential to translate to other microorganisms provided they possess an optical reporting trait.